Sustainability Of Petroleum And Environmental Control In The Malaysian Petroleum Law - Norfadhilah Mohd Ali (2024)
In supporting the international and local economic development, energy has become an inevitable factor. Despite the priority to gain more energy supply, in this paper’s concern – the petroleum, there is another priority which should not be neglected; that is policing it. This is to ensure its sustenance for both today and tomorrow generation as well as the environment. This paper seeks to analyse the existing Malaysian petroleum legislations and other relevant laws which promotes sustainability of petroleum and environmental conservation.